The KGD Motif of Epstein-Barr Virus gH/gL Is Bifunctional, Orchestrating Infection of B Cells and Epithelial Cells - Jia Chen (American Society for Microbiology, 2012)
ABSTRACT Epstein-Barr virus (EBV), a member of the herpesvirus family, is the causative agent of common human infections and specific malignancies. EBV entry into target cells, including B cells and epithelial cells, requires the interaction of multiple virus-encoded glycoproteins. Glycoproteins H and L (gH/gL) cooperate with glycoprotein B (gB) to mediate fusion of the viral envelope with target cell membranes. Both the gH/gL complex and gB are required for fusion, whereas glycoprotein 42 (gp42) acts as a tropism switch and is required for B cell infection and inhibits epithelial cell infection. Our previous studies identified a prominent KGD motif located on the surface of gH/gL. In the current study, we found that this motif serves as a bifunctional domain on the surface of gH/gL that directs EBV fusion of B cells and epithelial cells. Mutation of the KGD motif to AAA decreased fusion with both epithelial and B cells and reduced the binding of gH/gL to epithelial cells and to gp42. We also demonstrate that deletion of amino acids 62 to 66 of gp42 selectively reduces binding to wild-type gH/gL, but not the KGD mutant, suggesting that the KGD motif of gH/gL interacts with the N-terminal amino acids 62 to 66 of gp42. IMPORTANCE Epithelial and B cells are the major targets of Epstein-Barr virus (EBV) infection in the human host. EBV utilizes different glycoprotein complexes to enter these cell types. For B cell fusion, EBV uses complexes containing gp42, gH/gL, and gB, whereas just gH/gL and gB are required for epithelial cell fusion. In the current study, a bifunctional domain consisting of a prominent KGD motif on the surface of the gH/gL structure was identified; this domain affects interactions with gp42 or epithelial receptors, ultimately dictating with which cell type virus-induced fusion can occur. These studies will lead to a better understanding of the mechanism of EBV-induced membrane fusion and herpesvirus-induced membrane fusion in general.